Pengaruh Konversi Lahan terhadap Kondisi Lingkungan di Wilayah Peri-urban Kota Semarang (Studi Kasus: Area Berkembang Kecamatan Gunungpati) - Dewi, Nurma Kumala; Rudiarto, Iwan (Magister Pembangunan Wilayah dan Kota,Undip, 2014)
The geographical limitations such as mountainous land and prone to landslide disaster makes land conversion become an important issues to be review including its impact on the environment. The purpose of this study is to examine how the effects of land conversion to the environmental conditions (namely land, water, and air) in there. Based on the research results, growing area of Gunungpati Sub-district experienced land conversion towards build up area at 28.02 hectares, or increase 39.5% in the last 11 years. The land conversion issue encourages the emergence of landslides in the settlement and residential area. Based on the overlay results of land suitability with built up landmap, about 129 ha (24%) of residential land located in the preservation area, that is creating landslide in residential area.The land conversion also affects to the reduction in water catchment areas resulting so that it reduce groundwater discharge, 22 of the 36 residents who have wells, said that their ground water surface is decreasing. In addition, the reduction in water catchment areas also means that there is an increase in run-off water. And estimate the increase in run-off water by 37.5% from 186,273.48 m3/days of rain. Therefore, the development should based on land suitability and carrying capacity to create a sustainable physic and geographical environment.